Absorbed aluminium is found with two cytosolic protein fractions, other than ferritin, in the rat duodenum. Issue 5 (May 1993) - Cochran, M; Goddard, G; Ramm, G; Ludwigson, N; Marshall, J; Halliday, J
Abstract : After in vivo perfusion of the upper intestine of the rat with a range of concentrations of aluminium chloride, entry of the metal into the portal system was only detected when the perfusate exceeded 400 mumol/l, suggesting a mucosal block. Using gel filtration of a mucosal cytosol extract, two consistently appearing aluminium peaks were identified which may represent aluminium binding proteins. Both were heat stable at 60 degrees C and had molecular sizes of about 700 (kilo daltons) (kD) and 17 kD respectively. The larger molecule was distinct from ferritin. Neither molecule associated with 59Fe nor 45Ca. It is suggested that the aluminium peaks are relatively specific aluminium binding proteins that have a scavenging role, reducing entry of the metal from the intestinal contents into the portal blood.